Emerging Technologies: Implications for the Nepalese Tourism Industry - Rashmi Acharya (ASEAN Journal on Hospitality and Tourism, 2021)
This paper intends to present the potential technologies for sustainable tourism development and promotion of Nepal. Based on secondary literature, various emerging technologies that help to reduce manual works, maximize productivity and ensure the physical security of entities have been explored in the paper. Similarly, some challenges of technological interventions and needful steps to overcome the obstacles are also illustrated. Moreover, this paper also addresses the impacts of the prevailing COVID- 19 crisis on tourism in Nepal and puts forward the needful suggestions to mitigate the crisis. It is hoped that this paper can be a reference to scholars, tourism stakeholders, and policymakers as it delivers plentiful information on the potentialities and feasibilities of ICT implementation in Nepal.